2013
DOI: 10.1007/s12253-013-9616-2
|View full text |Cite
|
Sign up to set email alerts
|

XRCC2 R188H (rs3218536), XRCC3 T241M (rs861539) and R243H (rs77381814) Single Nucleotide Polymorphisms in Cervical Cancer Risk

Abstract: Human Papillomavirus (HPV) is the main cause of cervical cancer and its precursor lesions. Transformation may be induced by several mechanisms, including oncogene activation and genome instability. Individual differences in DNA damage recognition and repair have been hypothesized to influence cervical cancer risk. The aim of this study was to evaluate whether the double strand break gene polymorphisms XRCC2 R188H G>A (rs3218536), XRCC3 T241M C>T (rs861539) and R243H G>A (rs77381814) are associated to cervical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 25 publications
(41 reference statements)
0
21
0
2
Order By: Relevance
“…On the other hand, determined that there were polymorphic regions that were more frequently associated with melanoma skin cancer than cancer occurring in head, neck, bladder, and breast cancer. Th erefore, the eff ect of the XRCC3 gene varies in diff erent cancer types [31][32][33][34][35]. A recent study conducted in Poland focused on same genomic regions and cancer type, and has shown that the regions of interest are associated with cancer [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, determined that there were polymorphic regions that were more frequently associated with melanoma skin cancer than cancer occurring in head, neck, bladder, and breast cancer. Th erefore, the eff ect of the XRCC3 gene varies in diff erent cancer types [31][32][33][34][35]. A recent study conducted in Poland focused on same genomic regions and cancer type, and has shown that the regions of interest are associated with cancer [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Manual search of references cited in 1 additional article, but it was excluded for lack of data about XRCC3 Thr241Met gene polymorphism of cervical cancer (Wang et al, 2009). Finally, a total of 5 relevant studies including 4 English articles (He et al, 2008;Settheetham-Ishida et al, 2011;Djansugurova et al, 2013;Perez et al, 2013) and 1 Chinese paper (Xiao et al, 2010) met the inclusion criteria for the meta-analysis (including a total of 806 cervical cancer cases and 850 controls). There were 3 studies of Asians (He et al, 2008;Xiao et al, 2009;Settheetham-Ishida et al, 2011) and 2 studies of Caucasians (Djansugurova et al, 2013;Perez Table 1.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…18,19 Some reports stated that XRCC2 (Arg188His) polymorphisms may be involved in repair of HPV related DNA damage in cervical cancer. 20 But the results were debatable where few observations were not consistent in terms to show association between polymorphisms of XRCC1 Arg194Trp and development of cervical cancer, while the influence of the Arg280His polymorphisms acted as protective factor for squamous cervical carcinoma and Arg399Gln polymorphism increased cervical carcinogenesis among women whose age at first delivery was 20 years. 21 Also, few studies form India have been carried out to investigate association of XRCC1 gene with CC risk especially from Northern India and Southern India but they did not lead to a broad strapping conclusions.…”
Section: Introductionmentioning
confidence: 99%